2020
DOI: 10.7717/peerj.8270
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the rare and endangered lycophyteIsoetes yunguiensis

Abstract: Background Isoetes yunguiensis Q. F. Wang & W. C. Taylor is a lycophyte of an ancient genus, and it is endemic to China. It is a first-class protected plant in China. This living fossil is used in paleoecology and studies on the evolution of Lycophytes in the Yunnan-Guizhou Plateau. In recent years, human activities have caused the disappearance of several wild populations, and the number of plants in the existing populations is low. Study of the genetic structure, distribution pattern, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
3
1
Order By: Relevance
“…We showed that I. cangae is composed of a single panmictic population with moderate genetic diversity and no inbreeding signal, contradicting the classical assumptions for a NES. Population genetics studies of Isoëtes species around the world have been reported different levels of genetic diversity in Isoëtes species, applying other genetic markers (Caplen & Werth, 2000;Chen et al, 2005;Kang et al, 2005;Kim et al, 2008;Gentili et al, 2010;Li et al, 2013;Stelt et al, 2017;Ma et al, 2019;Zheng et al, 2020). Santos et al (2020) also found a high genetic diversity using ISSR markers but the presence of a genetically differentiated on the North of the Amendoim Lake was not corroborated by our results.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…We showed that I. cangae is composed of a single panmictic population with moderate genetic diversity and no inbreeding signal, contradicting the classical assumptions for a NES. Population genetics studies of Isoëtes species around the world have been reported different levels of genetic diversity in Isoëtes species, applying other genetic markers (Caplen & Werth, 2000;Chen et al, 2005;Kang et al, 2005;Kim et al, 2008;Gentili et al, 2010;Li et al, 2013;Stelt et al, 2017;Ma et al, 2019;Zheng et al, 2020). Santos et al (2020) also found a high genetic diversity using ISSR markers but the presence of a genetically differentiated on the North of the Amendoim Lake was not corroborated by our results.…”
Section: Discussioncontrasting
confidence: 79%
“…Fragment Length Polymorphism (AFLP; Jung et al, 2014;Kang et al, 2005), Inter-Simple Single Repeat (ISSR; Gentili et al, 2010;Ma et al, 2019;Santos et al, 2020), microsatellites (Li et al, 2013;Stelt et al, 2017;Zheng et al, 2020), chloroplast DNA (Jung et al, 2014;Nunes et al, 2018;Zheng et al, 2020), or Random Amplified Polymorphic DNA (RAPD; Chen et al, 2007;Kim et al, 2008;Gentili et al, 2010). These studies have shown that some Isoëtes species are marked by low genetic diversity (Kang et al, 2005;Kim et al, 2008) and others by moderate and higher diversity (Gentili et al, 2010;Chen et al, 2012;Stelt et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the altitude-induced temperature change (decrease about 6℃ per 1000 meter elevation) was also an important factor affecting the distribution of plants (Rangwala & Miller, 2012). The Yunnan-Guizhou Plateau, bounded by the Wumeng Mountains, was divided into the Yunnan Plateau (altitude 3000-4000 m) and the Guizhou Plateau (altitude 2000-2400 m) (Zheng et al, 2020). In summer, the temperature of the Yunnan-Guizhou Plateau was lower than that of the same latitude region due to its higher altitude.…”
Section: Prediction Of Future Distribution Under Climate Changesmentioning
confidence: 99%
“…EST-SSR markers have been extensively developed for multiple purposes, like genetic diversity analysis [56], genetic improvement [57], species delimitation [58] and markerassisted breeding [59]. In this study, Ginkgo germplasm resources showed high genetic diversity (I = 0.993, Ho = 0.809, He = 0.566, H = 0.563) compared with other endangered species, such as Isoetes yunguiensis (mean Ho = 0.475, He = 0.463, I = 0.782 for EST-SSRs [60]) and economically important plants, e.g., Camellia reticulata (mean Ho = 0.242, He = 0.457 for EST-SSRs [61]), and the results on Ginkgo from other studies (H = 0.2408, I = 0.3599 for ISSR [62]; H = 0.21, I = 0.34 for AFLP [63]; H = 0.12, I = 0.19 for AFLP [64]; He = 0.3159, I = 0.4489 for RAPD [11]; He = 0.808 for SSR [14]).…”
Section: Genetic Diversity and Population Structure Of The 101 Ginkgo...mentioning
confidence: 99%